Efecto del incremento de la temperatura en la germinación de semillas, crecimiento y supervivencia de plántulas de Myrciaria dubia (H.B.K.) Mc Vaugh y Cedrela odorata L. en invernaderos, Iquitos – Perú, 2021 - Mundaca Ramirez, Antony (2023)
Global warming has accelerated due to increased greenhouse gas emissions in recent years. The increase in ambient temperature affects the emergence and growth of tropical plant species. The objective of this research was to evaluate the effect of increased temperature on the emergence and growth of seedlings of "Camu camu" (Myrciaria dubia (Kunth) McVaugh) and "Cedro" (Cedrela odorata L.), species of ecological and economic importance. The seedlings were placed in two greenhouses: "Control" greenhouse and "Hot" greenhouse. The average temperature of the "Control" greenhouse was 26.61±0.03 °C, the average temperature of the "Caliente" greenhouse was 28.24±0.03 °C and the average external ambient temperature was 26.09±0.03 °C. Seedling emergence was counted daily and subsequently analysed for percentage emergence, mean emergence time and emergence rate index. Seedling growth was evaluated at the end of the experiment, i.e. four months after the start of the growth experiment, and the growth in height, diameter at the base of the neck or stem and the number of leaves were measured. The growth indicators evaluated were plant height, diameter at the base of the stem and number of leaves. The results show that increasing temperature decreases the emergence of Myrciaria dubia seedlings, but the emergence period takes less days. However, increasing temperature increases the emergence of Cedrela odorata seedlings, but the emergence period takes more days. This shows that temperature does or does not alter seedling emergence differently for each species. On the other hand, the increase in temperature affects the height growth of both species, with the indicator being more sensitive to the increase in temperature.